EFFECT OF DIFFERENT CONCENTRATIONS OF LIQUID PALM SUGAR ON THE QUALITY CHARACTERISTICS AND GLUTAMIC ACID CONTAINMENT OF SQUID RUSIP (Loligo chinensis) - Elistia, Elistia; Sumardianto, Sumardianto; Romadhon, Romadhon (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2023)
Squid has amino acids that are good for eating and are processed into rusip. Rusip is a Bangka Belitung chilli sauce made from anchovies. This study aims to determine the effect of different concentrations of liquid palm sugar on the quality and glutamic acid content. The research used experimental laboratories with Completely Randomized Design. Parametric tests were analyzed using ANOVA and BNJ, non-parametric tests using Kruskal Wallis and Mann Whitney with a test level of 5%. In the Rusip study, liquid palm sugar concentrations of 10%, 12.5% and 15% were used, with 3 replications. Glutamic acid, pH, protein and hedonic parameters showed significant differences (P<5%). The parameters of total LAB, total sugar and water content had no significant difference (P>5%). The values of protein content were 17.25%-19.66%, moisture content 33.94%-38.39%, total sugar 5.16%-7.71%, glutamic acid 2.25%-3.30%, pH 5.87-5.90 and total LAB 1.1x104-5.3 x 104 cfu/g. Hedonic parameters for appearance were 3.24-3.76, flavour 3.41-4.00, aroma 3.14-4.00, texture 3.31-4.10. The best treatment was 15% liquid palm sugar with characteristics of brown colour, chewiness, fermentation smell and savour.